2010
DOI: 10.1093/cvr/cvq145
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial microvascular permeability, interstitial oedema, and compromised cardiac function

Abstract: The heart, perhaps more than any other organ, is exquisitely sensitive to increases in microvascular permeability and the accumulation of myocardial interstitial oedema fluid. Whereas some organs can cope with profound increases in the interstitial fluid volume or oedema formation without a compromise in function, heart function is significantly compromised with only a few percent increase in the interstitial fluid volume. This would be of little consequence if myocardial oedema were an uncommon pathology. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
139
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(145 citation statements)
references
References 70 publications
5
139
0
1
Order By: Relevance
“…Indeed, an increase in cardiac water content by as little as 2.5% leads to a 30% to 40% reduction in cardiac output. 42,43 Furthermore, the remarkable improvement of cardiac function seen with our lymphangiogenic therapy is likely attributable to a combination of both direct (interstitial fluid pressure normalization) and indirect (cardiac fibrosis) effects of limiting myocardial edema. Different from lymphatic networks in other organs, 44,45 notably the essential absence of smooth muscle cells on cardiac precollectors, and only sparse muscular cells on its collecting ducts, 30 the heart largely depends on extrinsic factors for regulation of its lymphatic drainage.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, an increase in cardiac water content by as little as 2.5% leads to a 30% to 40% reduction in cardiac output. 42,43 Furthermore, the remarkable improvement of cardiac function seen with our lymphangiogenic therapy is likely attributable to a combination of both direct (interstitial fluid pressure normalization) and indirect (cardiac fibrosis) effects of limiting myocardial edema. Different from lymphatic networks in other organs, 44,45 notably the essential absence of smooth muscle cells on cardiac precollectors, and only sparse muscular cells on its collecting ducts, 30 the heart largely depends on extrinsic factors for regulation of its lymphatic drainage.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, cardiac function is already significantly compromised once the interstitial fluid volume is moderately increased 2. Myocardial edema formation represents a major clinical problem and leads to vessel collapse, stunning of the myocardium, induction of arrhythmias, and impaired cardiac function.…”
Section: Introductionmentioning
confidence: 99%
“…Edema occurs in response to ischemia/reperfusion, inflammation, organ transplant rejection, or cardioplegic arrest during surgical interventions such as coronary artery bypass grafting 3. Following myocardial infarction (MI), vascular permeability (VP) across the microvascular endothelium is increased, resulting in persistent postischemic vasogenic edema 2, 4. Myocardial tissue in the border zone of the MI is partially perfused by collateral vessels, preventing necrosis of these acutely undersupplied myocardial regions.…”
Section: Introductionmentioning
confidence: 99%
“…While a host of soluble factors including growth factors, circulating lipids, and reactive oxygen species chemically signal to endothelial cells, hemodynamic forces locally and acutely regulate vascular permeability by remodeling endothelial cell-cell junctions and the cytoskeleton 6 . The shear stress of steady, laminar flow improves barrier integrity through stabilization of cell-cell junctions, while perfusion defects increase vascular permeability and contribute to pathogenesis of cardiovascular diseases including atherosclerosis 7 , stroke 8 , and myocardial infarction 9 . While in vitro studies have identified putative shear stress-responsive signaling pathways that mediate endothelial junction and cytoskeletal remodeling 7 , the mechanisms that link hemodynamic shear stress to the regulation of endothelial cell-cell junctions and vascular permeability remain unknown.…”
mentioning
confidence: 99%